Deriving health utility values from a randomized, double-blind, placebo-controlled trial of siltuximab in subjects with multicentric Castleman's disease. (2nd July 2016) - Vernon, Margaret; Robinson, Don; Trundell, Dylan; Ishak, Jack; Jen, Min-Hua; Brazier, John
Abstract: Purpose : To estimate health utility values, explore predictors of utility values, and estimate the quality-adjusted life years (Q.A.L.Y.s) gained by treatment in multicentric Castleman's disease (M.C.D.).Methods : The SF-36 was administered to 79 patients enrolled in a randomized, double-blind, placebo-controlled, multi-national study to determine the safety and efficacy of siltuximab plus best supportive care (B.S.C.) compared with B.S.C., in subjects with symptomatic M.C.D. Utility (SF-6D) scores were derived from the SF-36. Sensitivity analyses using utilities obtained by mapping the SF-36 to the EQ-5D were also conducted. Repeated measures, mixed effects models were conducted to estimate effects of treatment, responder status and ≥ Grade 3 adverse events (A.E.s) on changes in utility values over time, controlling for baseline utility value. Additionally, differential Q.A.L.Y. gain was assessed in the trial using multiple regression.Results : Patients on siltuximab and those who experienced a complete or partial response had higher mean utility values over time than those on placebo or those with stable disease. After an initial response to treatment, the mean utility remained relatively stable for patients on siltuximab and those who experienced a complete or partial response during the period when most patients were on study. A significantly different Q.A.L.Y. gain was found for patients on siltuximab (versus placebo) as calculated by SF-6D (0.070 Q.A.L.Y.s, p  < .05) scores at 6 months (EQ-5D 0.096 Q.A.L.Y.s, p  < 0.05).Conclusions : Siltuximab demonstrated improved, durable health utility gains in this rare disease over B.S.C. The main SF-6D results were supported by EQ-5D sensitivity analysis. These findings are limited by the small study sample size and substantial missing data caused predominantly by crossover. A longitudinal, multisite international observational study capturing clinical, safety and health-related quality of life (H.R.Q.L.) endpoints are needed to confirm these findings.